LEADERS’ PORTFOLIO: PSYCHO-SOCIAL MECHANISMS AUGMENTING CREATIVITY - Praszkier, Ryszard (Journal of Positive Management, 2019)
Purpose: There is a consensus that creativity is one of the pivotal characteristics of a contemporary leader. There are however no publications indicating how the leader may augment own, as well as the team’s creativity. The article fills this gap, focusing on the type of creativity which is a long-lasting propensity – as opposed to one creative act usually considered in literature. Approach: The article is based on literature review and case studies analysis. After presenting cases illustrating the role of and need for creativity as a longitudinal propensity, a literature analysis follows delineating the mechanisms regulating creativity. We outline the role of brain plasticity in establishing the process of “being creative” as an enduring characteristic, as well as the ambient factors augmenting creativity. Findings: We focus on how to sustain a lasting creative state of mind (as opposed to performing single creative acts) and examine the factors that maintain the creative drive. We look at affective, cognitive and ambient mechanisms that enhance creativity. We specifically look at the role of joy (affective), distance (cognitive) and ambient factors (horizontal networks). We also review several techniques for enhancing teams’ creativity and conclude with recommendations for further studies. Implications: The article provides information useful for leaders and their teams, delineating ways of enhancing creativity. Value/Originality: The article presents a new approach to creativity as enduring phenomenon and to ways of augmenting creativity.